THE CONSUMER OR THE TRADER – WHO DECIDES ON HOW A PRODUCT IS USED? An analysis of the application of excise duty exemptions under Directive 92/83/EEC to alcohol - Mickutė, Karolina (Vilnius University Open Series, 2023)
Twenty-two years after adopting Directive 92/83/EEC, the European Commission initiated a review of the Directive because it did not correspond with the developments and the challenges, they pose for the alcohol sector. After six years of deliberation, amendments to Article 27.1. of the Directive entered into force this year, which, according to the study, will not address the critical problems with the Directive’s application. The research analyses the concept of ‘not for human use or consumption’, the interpretation of which had been identified by experts and the EC as problematic and detrimental not only to the interests of Member States but also to their residents and legal entities. In particular, the study found that official sources and national systems use definitions that are linguistically and substantively different, which does not ensure homogeneity in the application of the Directive, which is one of the EC’s priority objectives (harmonisation of the excise duty regime).The second part of the study asks whether the Court of Justice of the European Union (CJEU) can resolve the problems of the article’s interpretation. The case law on classifying products for taxation purposes is inconsistent and fragmented, selectively applied, and the judgments are often diagonally opposed. In one case, the CJEU relied on the consumer behaviour argument. In contrast, in another case, the Court held that the trader alone decides on the use of the product and that consumer behaviour is entirely irrelevant. This case is unique because the court legalised fraudulent schemes in selling surrogate alcohol, which is contrary to the EU’s goals to prevent health risks.Given that neither the CJEU nor legislative review and amendment can effectively ensure that the issue of excise duty is harmonised, the study invites us to explore the possibilities of changing the methodology on how court decisions are made. In particular, whether the issue of excise duty exemptions could be addressed by applying economic science. The study explores the concept of ‘not for human use or consumption’ by using the methodologies of mainstream post-Keynesian economic theory and mainline Austrian economic theory. The study finds that an analysis of consumer behaviour would ensure an effective interpretation of Article 27.1. of the Directive.
Keywords: EU law; excise taxes; not for human consumption; surrogate alcohol; CEE; economic analysis of law